2009
DOI: 10.2353/ajpath.2009.080516
|View full text |Cite
|
Sign up to set email alerts
|

Monokine Induced by Interferon-γ (MIG/CXCL9) Is Derived from Both Donor and Recipient Sources during Rejection of Class II Major Histocompatibility Complex Disparate Skin Allografts

Abstract: Chemokines, including monokine induced by interferon-␥ (Mig/CXCL9), are produced both in allografts and during the direct T-cell infiltration that mediates graft rejection. Neither the specific production nor contribution of allograft donor versus recipient Mig in allograft rejection is currently known. C57BL/6 mice with a targeted deletion in the Mig gene were used as both skin allograft donors and recipients in a class II major histocompatibility complex-mismatched graft model to test the requirement for don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…Interestingly, the recipients of WT hepatocytes had a significantly increased early production of CXCL9 (MIG) and CCL3 (MIP-1α) compared to those receiving CD47KO hepatocytes. These data are somewhat contradictory to previous studies showing that increased CXCL9 production is associated with enhanced alloresponses 22 23 24 . Although CCL3 might be upregulated during allograft rejection 24 , it was also reported to induce T cell apoptosis 25 .…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the recipients of WT hepatocytes had a significantly increased early production of CXCL9 (MIG) and CCL3 (MIP-1α) compared to those receiving CD47KO hepatocytes. These data are somewhat contradictory to previous studies showing that increased CXCL9 production is associated with enhanced alloresponses 22 23 24 . Although CCL3 might be upregulated during allograft rejection 24 , it was also reported to induce T cell apoptosis 25 .…”
Section: Discussioncontrasting
confidence: 99%
“…Second, IFN-γ plays an indispensable role in this particular transplant setting by up-regulating the expression of the single MHC class II alloantigen on donor keratinocytes [16]. Finally, CXCL9 and CXCL10, two chemokines induced by IFN-γ are required for tissue damages in this allogeneic combination [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the elevated expression of the CXCR3‐binding chemokines in clinical acute rejection samples and the results of studies in murine models of transplantation in which this chemokine axis was genetically manipulated, would suggest that CXCR3 and its ligands are involved in recruiting effector T cells to the graft parenchyma [28,37,47–49]. Furthermore, a recent study demonstrated that CXCL9 from both donor and recipient sources would act in synergy during rejection of class II major histocompatibility complex disparate skin allografts [50].…”
Section: Discussionmentioning
confidence: 99%